New high-tech biocomplex for the correction of metabolism disorders at diabetes - M. I. Kalimullin; S. S. Sady; A. N. Austrievskikh; V. M. Poznyakovsky (Новые технологии, 2019)
Relevance. Development of specialized food products of various functional purpose for the prevention and complex treatment of common diseases is one of the strategic directions for the development of modern nutrition. Of particular relevance is the creation of new high-tech biocomplexes in the form of dietary supplements (BAA), taking into account that this way is the most accessible and effective in solving the considered problem. The purpose of the study is to develop, determine regulated quality indicators and functional properties of a specialized product for the correction of metabolic processes in diabetes mellitus (DM). The methods. General laboratory and special methods of studying the quality and effectiveness of dietary supplements have been used: micronutrients have been determined using spectrophotometry and high performance liquid chromatography; assessment of carbohydrate metabolism - the methods of studying the basal, post-food glycemia and blood biochemical parameters. The results. The qualitative and quantitative composition of the dietary supplement formula the ingredients of which have targeted synergistic properties in relation to the normalization of carbohydrate metabolism disorders has been scientifically substantiated. Regulated indicators of nutritional value, characterizing functional properties, mg per 1 capsule have been determined: vitamin C - 22.5; Vitamin E - 3.75; vitamin B3 - 5,0; zinc - 2.0; manganese - 0.34; chromium - 6.25; betulin - 10.0; lipoic acid - 7.5; quercetin - 5.0; rutin - 5.0; tannins - 15.0. The terms and conditions of storage have been set at 3 years at a temperature not higher than 25°C in a dry, dark place. Clinical evidence of the effectiveness and functional orientation of the developed product through its use in the complex treatment of patients with type II diabetes has been presented. Conclusions.Recommendations for the use have been developed: 1 capsule 4 times a day, which ensures normalization of carbohydrate and lipid metabolism, biochemical parameters and endothelial dysfunction. The formulation and technology of dietary supplements have been tested in the production conditions of the enterprises of the Art Life company (Tomsk).